Industrial chemical cleaning - McCoy, James W. (Chemical Pub. Co., 1984)
Lucid and practical presentation of the problems and solutions to industrial chemical cleaning. This essential reference examines the causes and composition of fouling, the various chemicals used for its control, hazards in cleaning, and an examination of cleaning methods for the most common industrial equipment. Includes a complete section on the chemical analysis of deposits and the procedures for determining the most effective cleaning solutions. A main reference tool for the industrial engineer who manages equipment cleaning operations and the consultant who is called in to do the job.